Electronic games dependency: the possibility of a new psychiatric diagnosis (Archives of Clinical Psychiatry, 2012)
BACKGROUND: The practice of electronic games has been disconnected from a merely playful character, as its excessive use may be considered as a new psychiatric disorder. OBJECTIVE: To accomplish a review of the scientific literature concerning this possible dependence, addressing its main characteristics, worldwide prevalence and the possibility of comorbidities, and to evaluate the existence of treatment procedures based on cognitive behavioral therapy. METHOD: The research was conducted for articles published between 2001 and June 2011, using the PubMed, BVS, Lilacs and SciELO databases. RESULTS: There is no consensus whether the electronic game dependence is affiliated with the impulse control disorder group or chemical dependence. But it is known that the worldwide prevalence of this dependence has an average of 3%, with male predominance, and that there exist comorbidities of electronic game and chemical dependence. The cognitive behavioral therapy is already used as a possible treatment with effective short-term results. DISCUSSION: Despite dependence on electronic games is not considered as a specific diagnosis, this new phenomenon should be discussed and deepened in the scientific literature, seeking, in parallel, an efficient model of psychotherapeutic and pharmacological treatment.